AGE OF FUSION OF XIPHISTERNUM IN DELHI CITY OF INDIA A DIGITAL RADIOGRAPHIC STUDY (Journal of Forensic Medicine & Toxicology, 2017)
Identification is the determination of the individuality of an individual, living or dead. Age is one of the parameters used for identification of the deceased. Aim of the present study was to estimate age of fusion of xiphisternum with body of the sternum bone in dead bodies brought to mortuary of University College of Medical Sciences & Guru Teg Bahadur Hospital Delhi. A total of 150 intact sternum were digitally radio graphed in both AP (antero posterior) & Lateral view and studied. No significant difference in age of fusion in male and female was found. The mean age of complete fusion of xiphisternum was 49.74 years & 50.93 years in males and females respectively. AP view was found to be superior for examination of fusion in comparison to Lateral view of sternum bone.
Keywords: Age; fusion; manubrium; xiphisternum; digital radiograph